Simulated rain addition modifies diurnal patterns and temperature sensitivities of autotrophic and heterotrophic soil respiration in an arid desert ecosystem. (March 2015) - Song, Weimin; Chen, Shiping; Wu, Bo; Zhu, Yajuan; Zhou, Yadan; Lu, Qi; Lin, Guanghui
Abstract: The timing and magnitude of rainfall events in arid and semiarid regions are expected to change dramatically in future decades, which will likely greatly affect regional carbon cycles. To understand how increases in rainfall affect the diurnal patterns and temperature sensitivities (Q10 ) of soil respiration (RS ) and its key components (i.e. heterotrophic respiration (RH ) and autotrophic respiration (RA )), we conducted a manipulative field experiment in a desert ecosystem of Northwest China. We simulated five different scenarios of future rain regimes (0%, 25%, 50%, 75% and 100% increase over local annual mean precipitation) each month from May to September in 2009. We measured RS and RH every three hours on 6 and 16 days after the rain addition, and estimated RA by calculating the difference between RS and RH. We found that rain addition significantly increased the daily mean RS and its components on the two measurement days during the growing season. However, the diurnal pattern was different between the two respiration components. Rain addition significantly increased the daily Q10 value of RH but suppressed that of RA on Day 6. Rain addition had no influence on daily Q10 value of both respiration components on Day 16 when soil moisture was lower. In addition, we observed significantly higher daily Q10 of RH than RA under all five rain addition treatments, indicating that microbial respiration is more temperature sensitive than root respiration in a short-time scale in this desert ecosystem. Thus, partitioning soil respiration into its two components, and analyzing the differential responses of RH and RA to future climate changes should be considered for more accurate predictions of soil respiration and regional carbon cycle in these arid and semiarid regions. Highlights: Rain addition modified the diurnal patterns of soil respiration components. Rain addition increased the Q10 of microbial respiration on Day 6, but not on Day 16. Rain addition decreased the Q10 of root respiration on Day 6, but not on Day 16.